Utilization and Outcomes of BRCA Genetic Testing and Counseling in a National Commercially Insured Population: The ABOUT Study. Issue 5 (May 2016) - Armstrong, Joanne; Toscano, Michele; Kotchko, Nancy; Friedman, Sue; Schwartz, Marc D.; Virgo, Katherine S.; Lynch, Kristian; Andrews, James E.; Aguado Loi, Claudia X.; Bauer, Joseph E.; Casares, Carolina; Bourquardez Clark, Elizabeth; et al.
Abstract : Abstracted from JAMA Oncol 2015;1:1251–1260 The aims of this study were to identify factors associated with use of BRCA testing and to determine whether current genetic counseling referral and testing services in a community setting adhere to recommended professional guidelines.